Human papillomavirus genotype prevalence in cervical biopsies from women diagnosed with cervical intraepithelial neoplasia or cervical cancer in Melbourne, Australia. Issue 3 (1st April 2006) - Stevens, M. P.; Tabrizi, S. N.; Quinn, M. A.; Garland, S. M.
Abstract : Multicenter international phase III clinical trials using multivalent human papillomavirus (HPV) vaccines for cervical cancer (CC) prevention are underway. As HPV immunity is type specific, defining HPV genotype prevalence in different regions to ascertain whether predominant types differ geographically is considerably important prior to vaccine implementation. This study aimed to define HPV genotypes present in CC and high-grade dysplasia among women in Melbourne, Australia. HPV genotype analysis of a cross section of women in Melbourne with cervical dysplasia/cancer was performed. A total of 493 cervical biopsies from patients being treated for moderate ( n = 122) or severe ( n = 180) cervical intraepithelial neoplasia (CIN II/III) or CC ( n = 191) were tested for HPV genotypes using the PGMY09/11 primer system and line blot assay. HPV detection rates were 63.9%, 72.8%, and 86.9% in CIN II, CIN III, and CC biopsies, respectively. The most prevalent HPV genotypes among CC biopsies were HPV-16 (52.9%), HPV-18 (18.3%), HPV-45 (6.3%), HPV-39 (3.1%), and HPV-73 (2.6%). Multiple HPV infections, comprising two to five types, were identified in 14.4% of biopsies, being significantly fewer (5.2%) among CC biopsies ( P < 0.0001). These results indicate that the two most prevalent CC-associated HPV genotypes in Australia parallel those described internationally, with type variations thereafter.